Replication Data for: Tree biodiversity and carbon stocks of different agroforestry systems in Nicaragua - Siles, Pablo; Valbuena, Diego; Tellez, Orlando; Bonilla, Glenda; Morales, Teresa; Hoek, Rein van der; Castro, Aracely; Pulleman, Mirjam Margreet (International Center for Tropical Agriculture, 2018)
This study was aimed at quantifying the potential short-term impact of agroforestry-based systems on tree diversity and above and belowground carbon stocks in two representative SDTF sites in northern Nicaragua. Five land-use types were compared on 10 different farms across the two sites: Traditional slash–and-burn cropping systems (TCS), traditional pastures systems (TPS), SPS, QSMAS, and secondary forest (SF). Tree density, species composition, species richness and above and belowground (0-20cm depth) carbon pools and stocks were determined in 90 plots (0.1 ha each) in each of the five land-uses.